Analisis Kesalahan Penggunaan Joshi???Wa Dan ???Ga Dalam Kalimat Bahasa Jepang - Mohammad Faizal Fuad Aziz (Journal of Research in Foreign Language Teaching (JRFLT), 2018)
This study aims to analyze the mistake of joshi ??? wa and ??? ga. This research is a qualitative research. The method used in this research is descriptive analysis. Sources of data in this study is a second semester student Unipdu academic year 2017-2018. Data in this research is a matter that has been done by research subject. Technique of collecting data using test. The result of the research shows that there is one kind of mistake made by the students, that is the form of the kondoo error (alternating form) or the alternate form which has two variations of error form, that is exchange between the use of joshi ??? with joshi ??? their respective functions. In one function there are some problems that have the same function, namely the form of error swapped from joshi ??? because students still do not understand the meaning of the sentence.